Metazoan Parasites of Mozambique tilapia (Oreochromis mossambicus) Native to Lake Urema, Mozambique - Willem J. Smit; Maarten P. M. Vanhove; Ngonidzashe A. G. Moyo; Wilmien J. Luus-Powell (Fishes, 2023)
Mozambique tilapia Oreochromis mossambicus (Peters, 1852), an important aquaculture species investigated herein, is at risk and listed as vulnerable on the IUCN Red List. During a preliminary survey conducted in 2011, 30 Mozambique tilapia from Lake Urema in Gorongosa National Park in central Mozambique, were examined for metazoan parasites. Two groups of ectoparasites were recovered consisting of two species of copepods and a monogenean. Endoparasites retrieved were in the larval stage and included one trematode and one nematode species. This study provides new parasite records for O. mossambicus in Mozambique and forms a baseline for monitoring against the presence of ichthyoparasites associated with the introduction in neighbouring systems of non-native fish such as Nile tilapia Oreochromis niloticus (Linnaeus, 1758), a fish of worldwide importance in capture fisheries and especially aquaculture.